Pelatihan dan Sosialisasi Penggunaan Aplikasi Perhitungan Struktur Gedung (SAP2000) - Nella Asyifa, Cut; Idris, Yunita; Amalia, Zahra; Darma, Yusria (Universitas Syiah Kuala, 2024)
The advancement of modern civil engineering, software designed to facilitate and expedite the structural analysis calculation process, especially for seismic analysis, is also becoming increasingly sophisticated. The presence of this software greatly facilitates civil engineers in conducting analyses. Conducting seismic analysis for tall buildings using hand calculations not only consumes a significant amount of time and effort but also increases the risk of calculation errors due to human error. Training and Socialization on the Use of Building Structure Calculation Applications (SAP2000) were conducted offline in the Computer Laboratory Room of the MRK Civil Engineering Department, Faculty of Engineering, Syiah Kuala University. In general, the training and socialization materials on the use of building structure calculation applications, included an Introduction to Application Features, Modeling Steps, Continuous Beam Modeling Tutorial, 2D Frame Modeling Tutorial, and 3D Frame Modeling Tutorial. Based on the monitoring during the training, the participants showed great enthusiasm. They highly appreciated this activity as it provided them with the opportunity to learn about building structure calculations, and there were requests for further training sessions. After the completion of the activity, the participants were asked to fill out a questionnaire regarding the effects of using the application. One of the questions asked was about the participants' understanding after the training, where 100% of the participants reported an improvement in understanding due to the training activities.